Manufacturability Assessment of the Product Assembly Processes Design in the Automotive Industry - Jozef Matuszek; Tomasz Seneta; Luboslav Dulina; Eleonora Bigosova (Communications - Scientific letters of the University of Zilina, 2020)
The paper presents a methodology for the design of the production process of a new product from the point of view of manufacturability criterion assembly operations (Design for Assembly - DFA) in the automotive industry. Methods and techniques, used in implementation of the DFA method to produce a new product, are mentioned. Impact of those methods on improving the assembly technology of a complex product is described. Suggestions for improving the abovementioned methods are presented, as ell. The examples given illustrate the proposed procedures.